1997
DOI: 10.1007/s004010050627
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cortex blood flow and vascular smooth muscle contractility in a rat model of ischemia: a correlative laser Doppler flowmetric and scanning electron microscopic study

Abstract: The present study was undertaken to ascertain the role of smooth muscles and pericytes in the microcirculation during hyperperfusion and hypoperfusion following ischemia in rats. Paired external carotids, the pterygopalatine branch of the internal carotids and the basilar artery were exposed and divided. Reversible inflatable occluders were placed around the common carotids. After 24 h, the unanesthetized rat underwent 10-min ischemia by inflating the occluders. Continuous cortical cerebral blood flow (c-CBF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 69 publications
3
32
0
Order By: Relevance
“…Both male and female mice were used, and all mice used were between 2 and 5 months of age. To induce transgene expression in NG2-CreER mice, tamoxifen dissolved in corn oil/ethanol (9:1) was injected intraperitoneally at a dose of 100 mg/kg, every 24 h for 5 consecutive days (Madisen et al, 2010). These mice were then imaged within 2 weeks after the final tamoxifen injection.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both male and female mice were used, and all mice used were between 2 and 5 months of age. To induce transgene expression in NG2-CreER mice, tamoxifen dissolved in corn oil/ethanol (9:1) was injected intraperitoneally at a dose of 100 mg/kg, every 24 h for 5 consecutive days (Madisen et al, 2010). These mice were then imaged within 2 weeks after the final tamoxifen injection.…”
Section: Methodsmentioning
confidence: 99%
“…tdTomato reporter mice (Ai14) on a C57BL/6 background were purchased from The Jackson Laboratory (stock #007914; Madisen et al, 2010). These mice were bred with the following two different Cre driver lines to achieve transgene expression in pericytes: PDGFR␤-Cre mice (a gift from Volkhard Lindner, Maine Medical Center Research Institute, Portland, Maine;Cuttler et al, 2011) and neural/glial antigen 2 (NG2)-CreER mice (stock #008538, The Jackson Laboratory; Zhu et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it was observed that pericytes migrated from the vascular wall indicating morphological changes in response to brain damage such as ischaemia and traumatic brain injury (Takahashi et al 1997;Dore-Duffy et al 2000;Walski & Gajkowska 2001). Although we have no evidence for the involvement of capillary pericytes in the disruption of blood-brain barrier permeability caused by endothelin-1, the possibility cannot be entirely ruled out.…”
Section: Discussionmentioning
confidence: 99%